2013
DOI: 10.3945/ajcn.112.052951
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of zinc given as an adjunct in the treatment of severe and very severe pneumonia in hospitalized children 2–24 mo of age: a randomized, double-blind, placebo-controlled trial

Abstract: This study showed no overall benefit of the addition of zinc to antibiotics in reducing the time to recovery from pneumonia but showed a possible benefit of zinc supplementation in a subgroup of children with very severe pneumonia. Additional research is needed in specific subgroups such as children with very severe pneumonia. This trial was registered at http://www.controlled-trials.com as ISRCTN48954234.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 21 publications
5
43
0
Order By: Relevance
“…This promising finding was consistently confirmed by three other RCT (10,11) . However, the study conducted by Wadhwa et al (11) demonstrated that only very severe pneumonia rather than all severe pneumonia could benefit from Zn.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…This promising finding was consistently confirmed by three other RCT (10,11) . However, the study conducted by Wadhwa et al (11) demonstrated that only very severe pneumonia rather than all severe pneumonia could benefit from Zn.…”
Section: Introductionsupporting
confidence: 67%
“…Second, Zn might exacerbate the situation by the increased pro-inflammation while eradicating infection. Consistently, it was reported that Zn could decrease the case fatality and treatment failure without improving clinical recovery (11,35) , indicating that the benefit of Zn might be counteracted or alleviated by the detrimental effect from increased pro-inflammation. Third, the duration of Zn supplementation was relatively short, and the impaired immune response could not be reversed by such a short-time supplementation (17) .…”
Section: Potential Mechanismmentioning
confidence: 57%
See 2 more Smart Citations
“…The difference between both groups was highly significant (P<0.05) But Wadhwa et al found that zinc therapy is given or placebo is given, the death rate will be equal i.e., 1.5% with either method [25].…”
Section: Discussionmentioning
confidence: 99%